Neural mechanisms of maladaptive risk decision-making across psychiatric disorders - Cancan Lin; Yuhui Wang; Wenjie Xia; Defu Zhang; Xvbo Wang; Yue Wang; Yuxin Du; Hao Yu; Shanling Ji (Frontiers in Behavioral Neuroscience, 2025)
Risk decision-making is a fundamental cognitive process that involves distributed neural circuits, with impairments observed across various psychiatric conditions. This systematic review synthesizes current evidence on the neurobiological substrates underlying maladaptive risk processing, highlighting three key findings. First, frontostriatal dysregulation is identified as a central feature, characterized by prefrontal hypoactivation and striatal hyperreactivity, particularly prominent in bipolar disorder and addiction. Second, disorder-specific neural signatures are noted, such as insular dysfunction in anxiety disorders, ventral striatal blunting in depression, and orbitofrontal-insula decoupling in schizophrenia. Third, computational modeling reveals distinct alterations in risk sensitivity, loss aversion, and reward valuation parameters across different diagnostic categories. This review also evaluates principal assessment methodologies and therapeutic interventions. Future research should prioritize the integration of computational psychiatry with multimodal biomarkers to advance both theoretical models and clinical applications.